2001
DOI: 10.1002/ptr.719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aloe vera leaves on blood glucose level in type I and type II diabetic rat models

Abstract: Aloe vera (L.) Burm. fil. (= A. barbadensis Miller) (Liliaceae) is native to North Africa and also cultivated in Turkey. Aloes have long been used all over the world for their various medicinal properties. In the past 15 years, there have been controversial reports on the hypoglycaemic activity of Aloe species, probably due to differences in the parts of the plant used or to the model of diabetes chosen. In this study, separate experiments on three main groups of rats, namely, non-diabetic (ND), type I (IDDM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(104 citation statements)
references
References 20 publications
6
90
0
8
Order By: Relevance
“…Aloe vera possesses many health-promoting properties, including anti-inflammatory (Saito 1993;Vazquez et al 1996;Shimpo et al 2002), immunostimulant (Imanishi 1993;Qiu et al 2000), wound healing (Heggers et al 1995;Chitra et al 1998;Rajendran et al 2007), antiulcer (Koo 1994), antidiabetic (Ghannam et al 1986;Ajabnoor 1990;Beppu et al 1993;Okyar et al 2001;Rajesekaran et al 2004) and antitumour (Corsi et al 1998;Pecere et al 2000) in which the mediation of ROS levels could be involved. Werawatganon et al (2014) administered male mice with APAP (400 mg/kg) and Aloe vera (150 mg/kg).…”
Section: Aloe Barbadensis Millermentioning
confidence: 99%
“…Aloe vera possesses many health-promoting properties, including anti-inflammatory (Saito 1993;Vazquez et al 1996;Shimpo et al 2002), immunostimulant (Imanishi 1993;Qiu et al 2000), wound healing (Heggers et al 1995;Chitra et al 1998;Rajendran et al 2007), antiulcer (Koo 1994), antidiabetic (Ghannam et al 1986;Ajabnoor 1990;Beppu et al 1993;Okyar et al 2001;Rajesekaran et al 2004) and antitumour (Corsi et al 1998;Pecere et al 2000) in which the mediation of ROS levels could be involved. Werawatganon et al (2014) administered male mice with APAP (400 mg/kg) and Aloe vera (150 mg/kg).…”
Section: Aloe Barbadensis Millermentioning
confidence: 99%
“…In another study it was observed that Aloe vera successfully reduced the blood sugar as well as the blood triglyceride levels [237]. In a group of patients who were not responding to glibenclamide were given to Aloe vera and a 48% reduction in blood sugar levels and a 52% reduction in triglycerides was observed [239]. It is present in the anti diabetic polyherbal formulations namely GlucoCare Stevia rebaudiana, commonly known as sweet leaf, sugarleaf, or simply stevia, belongs to the family Asteraceae and is widely grown for its sweet leaves.…”
Section: Plants Possessing Hypoglycemic Activitymentioning
confidence: 95%
“…Another study reports the presence of inorganic trace elements (vanadium, zinc, copper; manganese and traces of chromium) in aloe leaf gel possessing hypoglycemic property, probably through improvement in impaired glucose tolerance thereby indirectly contributing to management of diabetes [238]. An experimental report states hypoglycemic activity on insulin dependent and non-insulin dependent rats with the effectiveness being enhanced for non-insulin dependent rats in comparison to glibenclamide [239]. In another study it was observed that Aloe vera successfully reduced the blood sugar as well as the blood triglyceride levels [237].…”
Section: Plants Possessing Hypoglycemic Activitymentioning
confidence: 99%
“…For example, aloe vera ingestion can enhance the hypoglycemic effect of glibenclamide. 3 St. John's wort has been reported to prolong emergence from anesthesia 4 and it may interact with cyclosporine resulting in transplant graft rejection. 5 The withdrawal from prolonged use of valerian, a sedative-hypnotic herb, can mimic that of a benzodiazepine withdrawal syndrome.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 99%
“…Commonly used herbal preparations thought to be innocuous may be associated with significant drug interactions. [3][4][5][6] Not only does some danger lie in taking these remedies themselves, but also in the fact that a number of patients do not inform their family physician that they are taking them. Even more importantly, since herbal medicine pharmacology was not included in the medical school curriculum when most physicians trained, few physicians are aware of the pharmacology of these medications, let alone the specific side-effects and drug interactions associated with their use.…”
mentioning
confidence: 99%